Human Rights as Battlefields
XVIII, 288 p.
Keywords: This book examines human rights as political battlefields, spaces that are undergoing constant changes in which political conflicts are expressed by a translation process within networks of interactions. This translation, in turn, contributes to modifying the scope and understanding of human rights. Ultimately, these battlefields express the legitimacy encounter of different versions of human rights in contemporary political practices. The volume thus challenges both the tendency to minimize the changing nature of human rights as well as the struggles emerging from the use of human rights discourses as a legitimization tool. By shifting the focus on what stakeholders do instead of solely on the origin, nature or foundations of human rights, the authors reveal that human rights are not static objects: they are constantly transformed and, as such, affect the horizon of universal rights. Gabriel Blouin-Genest is Assistant Professor of Political Science at Virginia Tech, USA. Marie-Christine Doran is Associate Professor of Comparative Politics at the School of Political Studies, University of Ottawa, Canada. Sylvie Paquerot is Associate Professor of Political and Legal Studies at the School of Political Studies, University of Ottawa, Canada.